Exploring the Socio-Demographic Predictors of Withholding Effort during Communicable Diseases Outbreak among Healthcare Workers in Ondo State, Nigeria - Popoola, Olusola Stella (Journal of Ecohumanism, 2025)
The survival of people during any communicable disease outbreak hangs on the withholding effort decision of healthcare workers (HCWs). This study examine the socio-demographic (age, sex, marital status, category of healthcare work, employment status, and years of experience) factors influencing HCW’s propensity to withhold effort during communicable disease outbreaks. A quantitative, cross-sectional survey was conducted among 477 HCWs from state specialist hospitals in Ondo State, South-western Nigeria. The findings revealed no significant difference in effort withholding between younger and older healthcare workers groups [t (474) =.18, p>.05]. In addition, socio-demographic factors [sex (t = -1.03, p > .05), marital status (t = -0.28, p > .05), category of healthcare work (t = -0.39, p > .05), employment status (t = -0.49, p > .05), and years of experience (t = 0.12, p > .05)], did not independently nor jointly [F (5,470) = 0.34, R² =.00, p>.05] predicted withholding of effort. The study recommends that organizations and policymakers should look beyond the socio-demographic attributes of HCWs when designing strategies to enhance HCWs' effort during preparedness for disease outbreaks. The study highlights the need for further research to explore factors, such as the availability of personal protective equipment (PPE), financial incentives, and organizational support, which may more strongly influence HCWs' behaviour during communicable diseases outbreaks.